Proposal of a modified technique of Nikolsky's sign in oral autoimmune vesiculobullous diseases - Petruzzi, Massimo (Frontiers in Oral Health, 2024)
Nikolsky's sign, originally described for skin lesions, presents challenges when applied to the oral mucosa. To address this, a modified Nikolsky's sign has been proposed specifically for the oral mucosa. In this variant, a gentle breath of air from the air syringe embedded in the dental unit is used to inflate a pre-existing collapsed blister (non-induced technique). Alternatively, in the induced technique, a healthy peri-lesion mucosal site is gently scratched with a blunt dental tool, and after a few minutes, air is blown on the same area to inflate any newly formed blister. The sign is considered positive if a blister is raised from the blown surface. The described modified Nikolsky's sign improves the visualization of oral vesicles and blisters in a cost-effective, easy, and minimally invasive manner. Its elicitation can aid in referring patients to specialized tertiary care units.